Trust and opportunistic behavior: the breach of contracts in the tobacco chain - Begnis, Heron Sergio Moreira; Arend, Silvio Cesar; Alievi, Rejane Maria (Revista de Administração da UFSM, 2017)
This study aimed to analyze the growers’ socioeconomic characteristics that are related to opportunistic behavior and contract breach in the tobacco productive chain in South Brazil. The nature of this research is predominantly quantitative and the data were collected through a survey with tobacco growers from the three states of South Brazil. Based on the literature of Transaction Costs Economics and inter-organizational relations, the analysis showed the main characteristics of the tobacco growers who are more likely to breach their contracts with the integrative companies.